Gender-specific association between serum uric acid levels and hypertension in East China: a cross-sectional study - Dan Liu; Xiang Zheng; Jing Zhu; Jianshu Yang; Li Lu; Xiaodong Ji; Jie Hui; Yongqin Luo (BMC Public Health)
Abstract Background This cross-sectional study aimed to investigate the correlation between serum uric acid (SUA) levels and the incidence of sex-specific high blood pressure in East China. Methods A total of 27,075 patients (14,399 males and 12,676 females) were enrolled in this study. The participants were grouped based on their SUA levels. Thereafter, the quartile (Q1-Q4) nodes of male SUA and female SUA were calculated based on the differences in the mean values of male and female SUA levels. The odds ratio (OR) and 95% confidence interval (CI) were calculated to evaluate the correlation between SUA and high blood pressure incidence. Results SUA expression levels were higher in males than in females. High SUA levels in males were positively correlated with hypertension. In females, high SUA levels were positively correlated with both hypertension and diabetes. After adjusting for confounding risk factors, SUA was confirmed as an independent risk factor for high blood pressure among males. Additionally, significant differences were observed between SUA and high blood pressure in body mass index (BMI) as well as diabetes subgroup analysis among males. There was a sex-specific correlation between SUA, high diastolic blood pressure (DBP), and high systolic blood pressure (SBP). Finally, there was a linear dose-response relationship between SUA and high blood pressure in males. Conclusion SUA is an independent risk factor for the incidence of high blood pressure after adjustment for other potential confounding risk factors in males. Sex-specific differences were also observed between SUA levels and high DBP or SBP.